ANALYSIS OF THE ROLE OF MIDWIVES IN ACHIEVING ANTENATAL K4 VISIT COVERAGE: A LITERATURE REVIEW - Irma Sagita S Halim; Werna Nontji; Mardiana Ahmad; Nur Aliya Arsyad (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2022)
Background: In Indonesia, this maternal mortality rate is still a major problem in the field of health. The high maternal mortality rate is related to the low quality of various programs in efforts to reduce AKI implemented by the government, namely Safe Motherhood, one of the pillars by improving access and quality of antenatal care services, namely on K4 visits that meet the National target of 90%. Objectives: This study aimed to analyze the role of Midwives in the achievement of K4 Visit coverage. Design: The method used in writing this article is the study of literature by descriptive methods. Data Sources: Search for articles using data-based ScienceDirect and Google Scholar by entering the keywords Antenatal care, Factors, Utilization, Pregnancy in the literature search section with inclusion criteria, namely articles discussing antenatal visits for pregnant women, published years 2018-2021, International Publications, articles using English, original article, full text and open access. Review Methods: The literature review method is in the form of a narrative review based on predetermined criteria, then collected and made a summary of the journal which includes the name of the researcher, the year of publication of the journal, the title of the study, the method, and a summary of the results or findings. The summary of the research journal is entered into a table according to the format. Results: From the search obtained 52,900 articles filtered the year obtained 16,900, journal selection based on inclusion criteria obtained by fourteen journals that are eligible for review. articles the journal review found that the role of health workers/midwives is one factor that can increase antenatal visits. A good role by health workers to pregnant women can make mothers realize the importance of making visits to increase the utilization of health services. Conclusion: The role of health workers/midwives is one of the factors that can increase antenatal k4 visits, namely by providing quality services, improving health promotion, and a friendly attitude full of concern for pregnant women's complaints. And it must be supported by complete skills, facilities, and infrastructure.